Phorbol ester-induced angiogenesis of endothelial progenitor cells: The role of NADPH oxidase-mediated, redox-related matrix metalloproteinase pathways - Wu, Tao-Cheng (PLoS One, 2019)
Endothelial progenitor cells (EPCs) may contribute to ischemia-induced angiogenesis in atherosclerotic diseases. The protein kinase C (PKC) family is involved in the regulation of angiogenesis, however the role of PKCα in EPCs during angiogenesis is unclear. The aim of this study was to evaluate the role of PKCα in EPCs during angiogenesis. Phorbol-12-myristate-13-acetate (PMA), a PKCα activator, significantly increased the activity and expression of matrix metalloproteinases (MMP) -2 and -9 in human (late outgrowth) EPCs in vitro. The MMPs promoted the migratory function and vascular formation of EPCs, which then contributed to neovascularization in a mouse hindlimb-ischemia model. Reactive oxygen species derived from nicotinamide adenine dinucleotide phosphate (NADPH) oxidase enhanced the expression of MMPs to increase the bioactivity of EPCs during angiogenesis. The mitogen-activated protein kinase (MAPK) signal pathway was associated with the activation of NADPH oxidase. PMA extensively activated the extracellular signal–regulated kinase (Erk) signal pathway to increase the expression of MMP-9. PMA also activated the p38, Erk, and c-Jun N-terminal kinase signal pathways to increase the expression of MMP-2. PMA-stimulated EPCs enhanced neovascularization in a mouse model of hindlimb ischemia via nuclear factor-κB translocation to up-regulation of the expression of MMP-2 and MMP-9. PMA could activate PKCα and promote the angiogenesis capacity of human EPCs via NADPH oxidase-mediated, redox-related, MMP-2 and MMP-9 pathways. The PKCα-activated, NADPH oxidase-mediated, redox-related MMP pathways could contribute to the function of human EPCs for ischemia-induced neovascularization, which may provide novel insights into the potential modification of EPCs for therapeutic angiogenesis.